Novel Hypovirulence-Associated RNA Mycovirus in the Plant-Pathogenic Fungus Botrytis cinerea: Molecular and Biological Characterization - Yu, Lin (Appl Environ Microbiol, 2015)
Botrytis cinerea is a pathogenic fungus causing gray mold on numerous economically important crops and ornamental plants. This study was conducted to characterize the biological and molecular features of a novel RNA mycovirus, Botrytis cinerea RNA virus 1 (BcRV1), in the hypovirulent strain BerBc-1 of B. cinerea. The genome of BcRV1 is 8,952 bp long with two putative overlapped open reading frames (ORFs), ORF1 and ORF2, coding for a hypothetical polypeptide (P1) and RNA-dependent RNA polymerase (RdRp), respectively. A −1 frameshifting region (designated the KNOT element) containing a shifty heptamer, a heptanucleotide spacer, and an H-type pseudoknot was predicted in the junction region of ORF1 and ORF2. The −1 frameshifting role of the KNOT element was experimentally confirmed through determination of the production of the fusion protein red fluorescent protein (RFP)-green fluorescent protein (GFP) by the plasmid containing the construct dsRed-KNOT-eGFP in Escherichia coli. BcRV1 belongs to a taxonomically unassigned double-stranded RNA (dsRNA) mycovirus group. It is closely related to grapevine-associated totivirus 2 and Sclerotinia sclerotiorum nonsegmented virus L. BcRV1 in strain BerBc-1 was found capable of being transmitted vertically through macroconidia and horizontally to other B. cinerea strains through hyphal contact. The presence of BcRV1 was found to be positively correlated with hypovirulence in B. cinerea, with the attenuation effects of BcRV1 on mycelial growth and pathogenicity being greatly affected by the accumulation level of BcRV1.